Zur Thams-cad-mkhyen-pa Chos-dbyiṅs-raṅ-grol gyi rnam thar theg mchog bstan paʼi śiṅ rta bźugs - Ṅag-dbaṅ-blo-bzaṅ-rgya-mtsho, Dalai Lama V, 1617-1682 (Kunsang Topgyel and Mani Dorji, 1979)
Biography of Zur Thams-cad-mkhyen-pa Chos-dbyiṅs-raṅgrol, guru of the 5th Dalai Lama Ṅag-dbaṅ-blo-bzaṅ-rgyamtsho.